A Longitudinal Portrait of California’s Kindergarten English Learners & Their Learning Outcomes - Sarah Novicoff; Sean F. Reardon; Rucker Johnson (AERA Open)
California’s K–12 funding and instructional policies for English learners have changed significantly over the past two decades. This paper uses student-level longitudinal data from 2006 to 2019 to examine the learning outcomes of successive cohorts of students who were classified as English learners in kindergarten as they progressed through California’s changing public school system. First, we find ELs grew more diverse linguistically over time. Second, we find that their third-grade achievement improved in math and English language arts and achievement gaps narrowed in both subjects. Third, we find that more recent cohorts reported slightly higher rates of English proficiency acquisition by the end of grade 5. Finally, we find that the proportion who were reclassified by grade 5 increased dramatically for the first two cohorts of our study but then remained constant for the next five years. In the most recent cohort we can observe, only 53% of students who entered kindergarten as ELs were reclassified by the end of grade 5.